Refleksi Moralitas dalam Keadilan Restoratif sebagai Alternatif Penyelesaian Tindak Pidana - Elvariani, Risma; Sunaryo, Sidik (Perhimpunan Sarjana Ekonomi dan Bisnis, 2025)
The retributive approach in Indonesia's criminal justice system has increasingly been challenged for failing to address the root causes of crime, victim needs, and offender rehabilitation. This study aims to explore restorative justice as a moral and philosophical alternative that emphasizes healing over punishment. It focuses on the correlation between justice and morality, reflecting how restorative practices contribute to a more humane and inclusive legal system. Using a philosophical-juridical method, the study examines statutory regulations including the Juvenile Criminal Justice System Law No. 11/2012, Prosecutor’s Regulation No. 15/2020, and Police Regulation No. 8/2021 and integrates them with the concepts of justice by Plato, moral responsibility by Poespoprodjo, and reintegrative shaming by Braithwaite. The findings highlight that restorative justice prioritizes repairing social harm, active accountability of offenders, and the empowerment of victims through participatory dialogue. Morality is manifested in the separation of wrongdoing from the wrongdoer, enabling moral transformation and social reintegration without stigmatization. While restorative principles have been partially adopted into national legislation, cultural and institutional resistance remains a challenge. Nonetheless, restorative justice emerges as a practical and ethical legal innovation capable of reducing recidivism, prison overcrowding, and distrust in the legal system. It offers not only a legal solution but a moral commitment to restoring social harmony.